Greg has 40 CD's and 20 DVD's. He sold 10 DVDs and 1/8 of his CD(40/8 = 5).
It is defined as the relation between two variables, if we plot the graph of the linear equation we will get a straight line.
If in the linear equation, one variable is present, then the equation is known as the linear equation in one variable.
It is given that:
Initially, Greg has a total of 60 DVDs and CDs in his collection.
He then sold 1/8 of his CDs and 1/2 of his DVDs.
Let the number of CD is c and DVD is d
c + d = 60
2(c/8) = d/2
d = 60 - c
4(2c/8) = 4(60-c)/2
c = 120 - 2c
c = 40
d = 60-40 = 20
Thus, Greg has 40 CD's and 20 DVD's. He sold 10 DVDs and 1/8 of his CD(40/8 = 5).
Learn more about the linear equation here:
#SPJ2
Answer:
10 DVD's were sold.
Step-by-step explanation:
c = number of CD's
d = number of DVD's
so we know:
c + d = 60
2*c/8 = d/2
this can be solved:
d = 60 - c
2c / 8 = (60-c)/2
4*(2c/8) = 4*(60-c)/2 [multiply by 4]
c = 120 - 2c
3c = 120
c = 40
d = 60-40 = 20
So Greg had 40 CD's and 20 DVD's. He sold half of his DVD's, i.e., 20/2=10 and 1/8 of his CD, i.e., 40/8 = 5
Answer:
Step-by-step explanation:
(Tangent Length)^2 = y*(y + 11) You are going to have to use the quadratic formula on this.
Tangent Length = 7
7^2 = y * (y + 11)
49 = y^2 + 11y
0 = y^2 + 11y - 49
a = 1
b = 11
c = - 49
When you solve this quadratic equation you get
x1 = 3.40 which is the answer you go with.
x2 = -14.40 which can't be used. A negative length has no meaning.
The value of the functionf(x) = 4x +5 at x = 5 is f(5) = 25
"It is a relation from a set of inputs to a set of possible outputs where each input is related to exactly one output."
For given example,
Given function: f(x) = 4x +5
We need to find the value of f(x)
This means, we need to find the function f(x) when x = 5
Substitute x = 5 in the given function.
⇒ f(x) = 4x +5
⇒ f(5) = 4(5) +5
⇒ f(5) = 20 + 5
⇒ f(5) = 25
Therefore, f(5) = 25
Learn more about the function here:
#SPJ2
Answer:
Step-by-step explanation:
~q → ~p
q → p
p → ~q
The logically equivalent statement to p → q is:
~q → ~p
The conditional statement:
p → q
p and q are propositions, then the conditional statement is can be written as:
So, always that p is true, q is also true, this means that if q is not true, then p must also not be true.
Then we can rewrite this using the negation propositions, which are:
~p and ~q
These mean:
Not p and Not q respectively.
Then the statement:
"If q is not true, then p is not true"
Is written as:
~q → ~p
So this is the logically equivalent statement.
If you want to learn more about statements, you can read: